2022
DOI: 10.1021/acsaem.1c03138
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Acetate Co-doping for Stable Carbon-Based CsPbIBr2 Solar Cells with Efficiency over 10.6%

Abstract: The all-inorganic CsPbIBr2 perovskite solar cells (PSCs) have been developed quickly in the past few years due to their photoelectric features and excellent stability. However, the disadvantages of high defect density and short carrier lifetime of CsPbIBr2 perovskites result in the inability to improve the power conversion efficiency (PCE) of batteries and hinder their practical application. Here, we prove that doping an appropriate amount of Zn­(Ac)2 (0.2%, at.) in CsPbIBr2 PSCs can improve crystal quality, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Device structure (optimized strategy) Fabrication technique (perovskite/carbon) According to valence states, B-site ions substitution can be divided into three types: Ag + (1.15 Å) ion substitution; [230] divalent substitution, such as Sn 2+ (0.93 Å), [99,231,232] Mg 2+ (0.72 Å), [233,234] Ca 2+ (1.00 Å), [234] Sr 2+ (1.12 Å), [234] Ba 2+ (1.35 Å), [234] Mn 2+ (0.67 Å), [100,235] Ni 2+ (0.69 Å), [235] Cu 2+ (0.73 Å), [235] Zn 2+ (0.74 Å), [235][236][237] and Cd 2+ (0.95 Å); [238,239] multivalent substitution, such as Sb 3+ (0.92 Å), [160] In 3+ (0.81 Å), [203,240,241] Bi 3+ (1.08 Å), [242] Nb 5+ (0.64 Å), [51] and lanthanide ions (e.g., Eu 2+ (1.17 Å), La 3+ (1.03 Å), Sm 3+ (0.96 Å), Tb 3+ (0.92 Å), Ho 3+ (0.90 Å), Er 3+ (0.89 Å), Yb 3+ (0.87 Å), etc.). [180,[243][244][245] Considering that Sn and Pb belong to IVA group and possess similar ns 2 np 2 electronic configuration and coordination geometry, partially substituting Pb 2+ with Sn 2+ was considered as the most effective strategy to optimize the optoelectronic properties of CsBX 3 .…”
Section: Perovskitementioning
confidence: 99%
See 1 more Smart Citation
“…Device structure (optimized strategy) Fabrication technique (perovskite/carbon) According to valence states, B-site ions substitution can be divided into three types: Ag + (1.15 Å) ion substitution; [230] divalent substitution, such as Sn 2+ (0.93 Å), [99,231,232] Mg 2+ (0.72 Å), [233,234] Ca 2+ (1.00 Å), [234] Sr 2+ (1.12 Å), [234] Ba 2+ (1.35 Å), [234] Mn 2+ (0.67 Å), [100,235] Ni 2+ (0.69 Å), [235] Cu 2+ (0.73 Å), [235] Zn 2+ (0.74 Å), [235][236][237] and Cd 2+ (0.95 Å); [238,239] multivalent substitution, such as Sb 3+ (0.92 Å), [160] In 3+ (0.81 Å), [203,240,241] Bi 3+ (1.08 Å), [242] Nb 5+ (0.64 Å), [51] and lanthanide ions (e.g., Eu 2+ (1.17 Å), La 3+ (1.03 Å), Sm 3+ (0.96 Å), Tb 3+ (0.92 Å), Ho 3+ (0.90 Å), Er 3+ (0.89 Å), Yb 3+ (0.87 Å), etc.). [180,[243][244][245] Considering that Sn and Pb belong to IVA group and possess similar ns 2 np 2 electronic configuration and coordination geometry, partially substituting Pb 2+ with Sn 2+ was considered as the most effective strategy to optimize the optoelectronic properties of CsBX 3 .…”
Section: Perovskitementioning
confidence: 99%
“…[249] The beneficial effects of Br − doping on V oc improvement is evident for CsSnI 3 devices even without the addition of SnF 2 . [81] Moreover, Cl − (1.81 Å), [250,251] SCN − (2.15-2.20 Å), [54,161,252] and Ac − (1.62 Å) [225,237] were also developed to dope CsPbX 3 . Compared with pristine CsPbBr 3 , doping with Cl − enlarged grain sizes, reduced defects, and optimized energy level alignment.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…HTM-free carbon-based CsPbIBr 2 PSCs have many of the advantages discussed earlier, but due to the energy level mismatch between the perovskite and the carbon electrode and a large number of defects at the interface between the materials, serious charge compounding greatly affects the performance of the carbon electrode. Based on this, researchers use strategies such as interface engineering and component engineering, which are usually used to suppress nonradiative recombination, optimize energy level matching, and improve device performance and stability. , For example, Wang et al introduced phthalimide (PTM) to improve the crystallization of perovskites, greatly improving the PCE of the device . 4-aminodiphenylamine (4-ADPA) was used by Chen et al to modify the surface and grain boundary of CsPbIBr 2 , and successfully combined with the uncoated lead ions on the surface to passivate the defects and achieve enhanced PCE .…”
Section: Introductionmentioning
confidence: 99%
“…Among these available strategies, cation doping/substitution is widely employed to tailor the optical/electronic properties and film quality of CsPbIBr 2 , which plays significant roles in creating homogeneous nucleation sites to control the crystallization and growth of CsPbIBr 2 crystals, contributing to remarkably enhanced perovskite film quality [ 58 , 59 , 60 ]. Nowadays, the cation doping in CsPbIBr 2 is mainly focused on the utilization of divalent metal cations to substitute Pb 2+ , including Sn 2+ , Cu 2+ , Zn 2+ , Ba 2+ , Eu 2+ , etc., which effectively enhance the crystallinity and morphology of CsPbIBr 2 films [ 61 , 62 , 63 , 64 , 65 , 66 ]. For instance, Sn 2+ plays a crucial role in regulating the band gap and enhancing the film quality of CsPbIBr 2 , and Zhao et al have reported that remarkably enhanced PCE (11.33%) and long-term stability were achieved by Sn 2+ doping in CsPbIBr 2 -based PSCs [ 61 , 64 ].…”
Section: Introductionmentioning
confidence: 99%